Perancangan Interior Graha Shinjuku Salon di Surabaya - Gunawan, Agung (Intra, 2015)
The beauty salon is a mandatory, especially for women to come and perform treatments to embellish and beautify the body, whether it is on healthy skin, hair beauty, facial aesthetics, nail care, and others. Graha Shinjuku Salon is one of the facility to serve the needs of consumers for hair beauty treatment which is located in the city of Surabaya. Provided facility services include hair cutting, coloring, rebonding, creambath, hair spa, smoothing, makeup, nail art, and others. In addition there is also a cafe, beauty salon, bridal, and also a photo studio to support the facility in Graha Shinjuku Salon.